An experimental study of the dynamic behavior of a 2 kW proton exchange membrane fuel cell stack under various loading conditions. (1st February 2015) - Jian, Qifei; Zhao, Yang; Wang, Haoting
Abstract: The dynamic behavior of the PEM (proton exchange membrane) fuel cell stack has great effect on the safety and effective operation of its applications. In this paper, a self-designed bulb-array is used to simulate the various loading conditions and study the dynamic behavior of a 2 kW PEM fuel cell stack. An evaluation index, including oscillation rate, pressure variation and dynamic resistance factor, is used to analyze the transient response of the PEM fuel cell stack. It is observed that the stack current increases about 8.6%, and the Oscillation rate decreases more rapidly after activation. In the step-up load stage, the oscillation rate and the dynamic resistance decrease more rapidly as the external load increases. Due to the periodic anodic purge process, a periodic voltage fluctuation can be seen. In addition, when the stack works in the open-loop state (working without the external load), the transient response of the stack current is significantly affected by the hydrogen humidity and the charge double-layer. Highlights: The working time of open-loop state significantly affects the transient response. Oscillation rate decreases faster as the external load increases. Dynamic resistance factor decreases as the external load increases. The periodic anodic purge process leads to a slight periodic oscillation of voltage.